Access to health care after dental trauma in children: A quantitative and qualitative evaluation. Issue 3 (18th March 2019) - Kayıllıoğlu Zencircioğlu, Özlem; Eden, Ece; Öcek, Zeliha Aslı
Abstract: Background/Aims: The aim of this study was to evaluate the accessibility of proper and on‐time treatment after dental trauma in children and to explore the affecting factors via parents' and health professionals' perspectives. The study is important to understand how to improve access to dental treatment after trauma. Materials and Method: The method included quantitative and qualitative parts. For the quantitative method, parents of dental trauma patients who applied to Ege University, Department of Pedodontics during January 2015‐June 2016 were the target group. One hundred and forty parents answered the questionnaire on trauma experiences. The participation rate was 62.78%. Questions covered variables such as first admitted health institution, time to go there, access to diagnostics, treatment methods, referral from institution, and sociodemographic characteristics of the family. On‐time and proper treatment access was defined using an algorithm for treatment priority of the case, total time to reach treatment, and the correct intervention. For the qualitative method, ten parents and thirty health professionals were interviewed in‐depth using a semi‐structured question guide. Thematic analysis was applied to the interview texts. Results: The percentage of patients who accessed on‐time and proper treatment was 19.29%. Logistic regression analysis showed that admission to the university clinic first increased the access to treatment by 14.135 times. For the qualitative evaluation, treatment access was summarized into three main themes: (a) physical accessibility of dental health services, (b) a quality dental health service as an outcome, and (c) communication among parties. Conclusion: The level of accessing proper and on‐time treatment was quite inadequate. It is suggested that distribution of dental care centers should be increased and dental centers where competent dentists work should be established. Performance‐based payment should be reorganized and cooperation between medical and dental institutions should be encouraged.